NMR study of acutanol, a new cembrene alcohol, and sarcophytol A isolated from the soft coral Sarcophyton acutangulum. Issue 3 (2001) - Mada Mada, Keiko Keiko; Ooi Ooi, Takashi Takashi; Kusumi Kusumi, Takenori Takenori
Abstract : A new cembrene alcohol, named acutanol, has been isolated from the soft coral, Sarcophyton acutangulum . Its structure has been determined on the basis of extensive NMR study. Absolute configuration of the major component, sarcophytol A, has been confirmed by use of a chiral anisotropic reagent, 1‒naphthylmethoxyacetic acid (1NMA).